ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEBELUM DAN SESUDAH MASA PANDEMI COVID-19 DI KELAS X MAN 1 TAPANULI TENGAH - Muhammad Akbar Apriadi; Rahmatika Elindra; Muhammad Syahril Harahap (JURNAL MathEdu (Mathematic Education Journal), 2021)
This study aimed to analyze students’ mathematical problem solving ability before and after pandemic Covid-19 period at the tenth grade students of MAN 1 Tapanuli Tengah. On line learning was used before pandemic Covid-19 period and offline was used after pandemic Covid-19 period. The research was conducted by applying qualitative descriptive method. Interview, questionnaire, and test were used in collecting the data. The data was analysis by applying data reduction, data presentation, and taking conclusion. The result of the research showed (1) the average of students’ mathematical problem solving ability before pandemic Covid-19 period (online learning) was 1.5 (enough category) and after pandemic Covid-19 period (offline learning) was 1.2 (fail category). It’s concluded online learning is not efficient used in pandemic Covid-19 period so we have to looking for the other solution in learning pandemic Covid-19 period.